2013
DOI: 10.6061/clinics/2013(07)15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with frailty in an older population from the city of Rio de Janeiro, Brazil: the FIBRA-RJ Study

Abstract: OBJECTIVE:Frailty syndrome can be defined as a state of vulnerability to stressors resulting from a decrease in functional reserve across multiple systems and compromising an individual's capacity to maintain homeostasis. The purpose of this study was to determine the prevalence of frailty and its association with social and demographic factors, functional capacity, cognitive status and self-reported comorbidities in a sample of community-dwelling older individuals who are clients of a healthcare plan.METHODS:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
81
6
22

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(135 citation statements)
references
References 46 publications
16
81
6
22
Order By: Relevance
“…Moreira and Lourenço 20 argued that only a history of three or more falls, which define the elderly individual as a faller, is directly linked to frailty, which may explain the lack of an association here, as in addition to the rate of falls being low, 80% of these elderly individuals had a history of only one fall. This study was limited by the exclusion of elderly people with cognitive impairment, which is considered a factor for the development of the syndrome of frailty.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Moreira and Lourenço 20 argued that only a history of three or more falls, which define the elderly individual as a faller, is directly linked to frailty, which may explain the lack of an association here, as in addition to the rate of falls being low, 80% of these elderly individuals had a history of only one fall. This study was limited by the exclusion of elderly people with cognitive impairment, which is considered a factor for the development of the syndrome of frailty.…”
Section: Discussionmentioning
confidence: 75%
“…9 The elderly persons interviewed in the present study had at least one comorbidity, mainly visual disorders, SAH, insomnia and OA. SAH and OA are among the chronic diseases associated with pain and/or FR= frail elderly persons; PF= pre-frail elderly persons; NF= non-frail elderly persons loss of function most commonly involved with the occurrence of frailty, 19 with heart, kidney and liver failure, cancer, diabetes mellitus, chronic obstructive pulmonary disease, stroke and atherosclerosis, 20 less cited in the present study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Peru (20) , there was no association between frailty and old age and falls in the prior year. In Brazil, researchers from Rio de Janeiro also found an association of frailty with advanced age, the presence of morbidities, and lower educational level (21) . A study performed in Ribeirão Preto (SP) showed that there was a greater chance of falling among the frail elderly, using EFS to diagnose the condition (22) .…”
Section: Discussionmentioning
confidence: 99%
“…In our study the sociodemographic factors associated with frailty were identified as age, female gender, low education status (literate), being a housewife, and living with the family. In the literature, especially age and female gender stand out as determining factors in frailty (Heuberger 2011;Jürschik et al 2012;Castell et al 2013;Hoover et al 2013;Kobayashi et al 2013;Moreira and Lourenço 2013;González-Vaca et al 2014;Runzer-Colmenares et al 2014). On the other hand, Oliveira et al (2013) did not report age and female gender as influential factors.…”
Section: Discussionmentioning
confidence: 99%